1998
DOI: 10.1097/00002030-199816000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Treatment history and baseline viral load, but not viral tropism or CCR-5 genotype, influence prolonged antiviral efficacy of highly active antiretroviral treatment

Abstract: The virological outcome after 1 year of HAART was strongly correlated to prior treatment history and baseline viral load, whereas CD4+ lymphocyte count, CCR-5 genotype and viral biological phenotype had less influence. The long-term antiviral efficacy of HAART was lowest in individuals with previous nucleoside analogue treatment and a high baseline viral load. In these individuals an even more aggressive treatment should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 49 publications
3
36
2
Order By: Relevance
“…Models 2b and 2c shown here correspond to multivariable models 1 and 2 in Table 5. VOL. 76,2002 INFLUENCE OF CHEMOKINE RECEPTOR GENOTYPES ON HIV/AIDS 669 genetic variation on HIV-1 RNA levels is probably more useful than it is on other outcome measures because of the dual impact of viral RNA levels on subsequent disease progression rates (5,28,47,57,66) and HIV-1 transmissibility from infected to uninfected individuals (17,18,56,58,60,65). Our work could not confirm other reported associations of CCR haplotypes and genotypes with clinical outcomes in HIV-1 infection.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Models 2b and 2c shown here correspond to multivariable models 1 and 2 in Table 5. VOL. 76,2002 INFLUENCE OF CHEMOKINE RECEPTOR GENOTYPES ON HIV/AIDS 669 genetic variation on HIV-1 RNA levels is probably more useful than it is on other outcome measures because of the dual impact of viral RNA levels on subsequent disease progression rates (5,28,47,57,66) and HIV-1 transmissibility from infected to uninfected individuals (17,18,56,58,60,65). Our work could not confirm other reported associations of CCR haplotypes and genotypes with clinical outcomes in HIV-1 infection.…”
Section: Discussionmentioning
confidence: 55%
“…The plasma HIV-1 RNA concentration measured in the months after untreated infection accurately reflects the early host-virus equilibrium (10,14,32,38,47,48), which in turn is highly predictive of the rate of later disease progression (5,9,28,47,57,66) as well as HIV-1 transmissibility from infected to uninfected individuals regardless of the transmission mode (17,18,56,58,60,65). Clinical and virological studies of the impact of chemokine receptor-ligand variants on viral dynamics have already suggested a role for ⌬32 and 64I in determining this equilibrium, apparently even in the context of antiretroviral therapy (4,22,31,53).…”
mentioning
confidence: 99%
“…Evaluation of host genetic influence on HIV-1 RNA levels should prove increasingly useful, because early in the course of infection, those levels have profound implications not only for the rate of subsequent progression of both untreated (4,28,43,50,61) and treated (4, 53, 54) disease but also for the transmissibility of HIV-1 from infected to uninfected individuals (12,14,49,51,55,59). If the three consistently favorable HLA markers (Table 7) prove more broadly protective in Zambians and other southern Africans, individuals carrying them should experience a relatively benign course of disease progression without treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We previously observed that the CCR5 D32 deletion was predictive of a higher immunological and virological response rate to HAART, at 6 and 12 months, in a population of 166 HIV-1-infected patients with advanced disease who were protease inhibitor naïve [23]. A better response in heterozygotes has also been observed in some studies [20,[24][25][26] but not in all [23,[27][28][29].To clarify the impact of the CCR5 D32 deletion on the response to HAART, we analysed here whether the presence of the CCR5 D32 allele affected the immunological and virological outcome after HAART initiation in a larger population of HIV-1-infected patients with a longer followup after HAART initiation; this longer follow-up allowed us to investigate whether D32 heterozygotes also had a better clinical prognosis after HAART initiation. …”
mentioning
confidence: 92%